2017
DOI: 10.1007/s00467-017-3707-3
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide conversion to generic tacrolimus in pediatric kidney transplant recipients

Abstract: Pediatric renal transplant recipients can be converted from Tacrolimus Prograf® to Sandoz® with negligible change in trough concentration, dose adjustments, or immediate allograft function. Of concern was the number of acute rejection episodes, however non-adherence contributed to at least one episode and this difference was determined clinically and statistically not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One of the studies already highlighted recruited small sample sizes (n = 2-10) due to the nature of study population, for example, patients with organ transplant (59). Risk factors of poor study design from the studies already identified include: non-randomized study design (44,62,67,103); parallel study arms (35); retrospective study design (104); methodology used in statistical results (e.g., partial AUC calculations were not considered for complex release methylphenidate formulations) (104), or baseline errors for endogenous molecules (e.g., levothyroxine ( 105)).…”
Section: Poor Study Design Including Small Sample Sizementioning
confidence: 99%
“…One of the studies already highlighted recruited small sample sizes (n = 2-10) due to the nature of study population, for example, patients with organ transplant (59). Risk factors of poor study design from the studies already identified include: non-randomized study design (44,62,67,103); parallel study arms (35); retrospective study design (104); methodology used in statistical results (e.g., partial AUC calculations were not considered for complex release methylphenidate formulations) (104), or baseline errors for endogenous molecules (e.g., levothyroxine ( 105)).…”
Section: Poor Study Design Including Small Sample Sizementioning
confidence: 99%
“…However, a lot of studies have been published in recent years about the successful use of generic tacrolimus by switching from the original product or de novo use after transplantation (3)(4)(5). It has also been reported that conversion to generic tacrolimus is safe in the pediatric kidney transplant patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of immunosuppressive therapy is most often performed on immunosuppressant blood levels that mirror the pharmacokinetics but not the pharmacodynamics. 8 Therefore, other potential methods to determine immune function and grade of immunosuppression, such as analysis of the Torque-Teno virus load 9 or virus-specific T cells (Tvis), 10 are currently evaluated. Tvis control virus replication and have been shown to correlate with virus-specific as well as general cellular immune defense, which represents the individual's susceptibility to infections.…”
mentioning
confidence: 99%